Hubungan Konsep Diri dengan Perilaku Agresif Remaja yang Belajar Pencak Silat - Robiatul Adawiyah; Estalita Kelly (Ilmu Psikologi Universitas Yudharta Pasuruan)
Aggressive behavior is a form of action with the intention of hurting and can harm other people which can have an impact on the individual as well as the victim (other people). Negative self concept will lead to insecurity and this can invite compensation by acting aggressively to objects around the individual who are based on an excessive sense of helplessness. This study aims to determine the relationship between self concept and aggressive behavior in adolescents who learn pencak silat. The subjects of the study were youths of pencak silat in Malang, 48 women and 27 boys. Data collection used in this study is a scale of aggressive behavior and a scale of self concept. The validity test results obtained 31 valid items for the aggressive behavior scale and 35 valid items for the self concept scale. The calculation of reliability on the scale of aggressive behavior and self concept was calculated using analysis of variance hoyt. Obtained is 0.993 for the scale of aggressive behavior and 0.983 for the scale of self concept. The data analysis was calculated using Product Moment Correlation analysis, it was obtained rxy of -0.89, which means that there is a very significant relationship between Self concept and Aggressive Behavior.